2010
DOI: 10.1007/s00268-010-0598-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Hepatic Resection and Transarterial Chemoembolization for Barcelona Clinic Liver Cancer (BCLC) Stage B Hepatocellular Carcinoma: Change for Treatment of Choice?

Abstract: Our study demonstrated that hepatic resection for BCLC stage B, Child A HCC patients had better survival rates than TACE group. Thus, hepatic resection is indicated in selected patients with BCLC stage B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 41 publications
(36 reference statements)
7
81
1
Order By: Relevance
“…In accordance with these findings, several studies found similar survival benefits of liver resection in the management of intermediate HCC [24][25][26][27][28][29][30][31] . Another group of investigators performed a propensity score study which enrolled patients with intermediate and advanced HCC, and observed survival benefits of liver resection by total analysis and propensity-matched analysis [29] .…”
Section: Liver Resection Vs Tace For Intermediate Hccsupporting
confidence: 68%
See 4 more Smart Citations
“…In accordance with these findings, several studies found similar survival benefits of liver resection in the management of intermediate HCC [24][25][26][27][28][29][30][31] . Another group of investigators performed a propensity score study which enrolled patients with intermediate and advanced HCC, and observed survival benefits of liver resection by total analysis and propensity-matched analysis [29] .…”
Section: Liver Resection Vs Tace For Intermediate Hccsupporting
confidence: 68%
“…Studies reached inconsistent findings about the mortality rates associated with each treatment strategy. Hsu et al [27] observed a higher mortality rate in the resection group than in the TACE group, which was contradicted by several other studies [26,29] . This could perhaps be explained by the fact that the proportion of patients aged < 65 years differed between the liver resection group and the TACE group, which likely biased the analysis of mortality.…”
Section: Liver Resection Vs Tace For Intermediate Hccmentioning
confidence: 89%
See 3 more Smart Citations